(untitled) (Revista Brasileira Multidisciplinar, 2024)
Brazil has a rich biodiversity and, in this context, Plinia cauliflora (jaboticaba) stands out as a native species with significant pharmacological potential. The plant is found in various regions of the country and has been studied for its diverse biological activities, including antioxidant, anti-inflammatory, vasodilator, antitumoral, antiparasitic, leishmanicidal, antidiarrheal, antiobesity and photoprotective properties. These activities are associated with the presence of phenolic compounds, such as anthocyanins, flavonoids, procyanidins, phenolic acids and tannins, present in the different parts of the plant. The popular use of P. cauliflora includes the treatment of various conditions, such as dysentery, diarrhea, inflammation, flu, bronchitis and labyrinthitis. In addition, jaboticaba fruits are consumed fresh and have demonstrated health benefits, including antioxidant effects and the reduction of serum glucose and insulin levels in healthy individuals. However, despite its traditional use, scientific research on the pharmacological properties of the leaves and branches of P. cauliflora are limited, which presents an opportunity for further study and exploration of its medicinal potential. This review article aims to describe the main pharmacological properties found in the literature about P. cauliflora, focusing on the plant parts: leaves, branches and fruits. The methodology used in the literature review included the following databases: Google Scholar, Scielo, Science Direct, Scopus, Periódico CAPES and PubMed; using keywords in both English and Portuguese language, such as "Plinia cauliflora", "Jaboticaba", "Jabuticabeira", "Myrciaria cauliflora", and synonyms. The prioritized scientific articles for data collection were those published in the last decade, between 2011 and 2023. The review underscores the importance of promoting better pharmacological utilization of all parts of P. cauliflora, encouraging future research on the chemical composition and biological activities of the plant.